Effectiveness of the Organic Acid-Based Antimicrobial Agent to Prevent Bacterial Contamination in Fish Meal - Wattana Pelyuntha; Ananya Yafa; Baramee Charoenwong; Kitiya Vongkamjan (Animals, 2022)
Animal feed production is an important step of the food animal production chain in a farm-to-table model. The contamination of raw ingredients with foodborne pathogens in feed production remains as an important safety issue where pathogens may spread into food animals to cause illnesses in humans when affected food animals are consumed. In the present study, we aimed to examine the quality and microbial contamination of fish meal and to investigate the effectiveness of the organic acid-based antimicrobial agent SALTEC 514TM against Salmonella to prevent bacterial contamination in fish meal. Fish meal samples (n = 4) collected from feed mills at different locations were analyzed for protein and total volatile basic nitrogen (TVBN) content to assess their nutritional value and freshness, and its microbiological quality. The protein and TVBN content ranged from 53.2 ± 3.1 to 67.5 ± 2.3 g/100 g and 73.8 ± 4.5 to 100.4 ± 11.2 mg/100 g meal, respectively. Total plate count of the fish meal samples ranged from 2.0 ± 0.3 to 4.5 ± 0.5 log units, whereas suspected foodborne bacteria, Escherichia coli and Salmonella, were not detected in all samples. Fish meal samples were artificially contaminated (day 0) and re-challenged (day 30 and 90) with Salmonella Enteritidis (3 log CFU/g) to test for the effectiveness of SALTEC 514TM, an organic acid-based antimicrobial formulation, in preventing Salmonella contamination and recontamination during storage. SALTEC 514TM, when applied at three different doses, was found to reduce the number of Salmonella in monitored samples after one day of storage. A low dose of 0.5 kg/ton SALTEC 514TM prevented Salmonella recontamination from occurring in fish meal samples stored for 37 days. In medium (1.0 kg/ton) and high doses (3.0 kg/ton), applications of SALTEC 514TM prevented the Salmonella recontamination for a maximum storage duration of 97 days. The application of SALTEC 514TM in fish meal and/or other feed ingredients may prove to be a safe alternative to reduce the microbial load, especially of foodborne-related microorganisms, to contribute to feed and food safety.